2018
DOI: 10.1161/jaha.117.008077
|View full text |Cite
|
Sign up to set email alerts
|

RIPHeart (Remote Ischemic Preconditioning for Heart Surgery) Study: Myocardial Dysfunction, Postoperative Neurocognitive Dysfunction, and 1 Year Follow‐Up

Abstract: BackgroundRemote ischemic preconditioning (RIPC) has been suggested to protect against certain forms of organ injury after cardiac surgery. Previously, we reported the main results of RIPHeart (Remote Ischemic Preconditioning for Heart Surgery) Study, a multicenter trial randomizing 1403 cardiac surgery patients receiving either RIPC or sham‐RIPC.Methods and ResultsIn this follow‐up paper, we present 1‐year follow‐up of the composite primary end point and its individual components (all‐cause mortality, myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 41 publications
1
75
0
1
Order By: Relevance
“…In addition, clinical studies also suggest that rIPC prevents the deterioration of short-term post-operative cognitive function in cardiac surgery patients [ 117 ], as well as reduces post-operative ischaemic tissue damage in brain tumour surgery [ 119 ]. However, the role of rIPC in neuroprotection has produced conflicting results, with findings from the multicentre, randomised RIPHeart (Remote Ischaemic Preconditioning for Heart Surgery) study demonstrating no effect on neurocognitive function or long-term outcomes in cardiac surgery patients [ 120 ].…”
Section: Therapeutic Options For Post-operative Neurological Complicamentioning
confidence: 99%
“…In addition, clinical studies also suggest that rIPC prevents the deterioration of short-term post-operative cognitive function in cardiac surgery patients [ 117 ], as well as reduces post-operative ischaemic tissue damage in brain tumour surgery [ 119 ]. However, the role of rIPC in neuroprotection has produced conflicting results, with findings from the multicentre, randomised RIPHeart (Remote Ischaemic Preconditioning for Heart Surgery) study demonstrating no effect on neurocognitive function or long-term outcomes in cardiac surgery patients [ 120 ].…”
Section: Therapeutic Options For Post-operative Neurological Complicamentioning
confidence: 99%
“…While this effect was confirmed by our preceding meta-analysis (see Yang et al [16]), in our study, mortality, morbidity, and other clinical outcomes were not improved. Additionally, several studies [1719], including two multicenter randomized clinical trials with a larger sample size in cardiac surgery reported by Hausenloy et al [18] and Meybohm et al [19], failed to demonstrate that RIPC exerts beneficial effects in this type of patient.…”
Section: Discussionmentioning
confidence: 99%
“…Bypass Graft Surgery trial) did not nd renoprotective effects of RIPC, and the result was maintained up to 1 year after the surgery in the Remote Ischemic Preconditioning for Heart Surgery study [6]. However, Zarbock and colleagues demonstrated that RIPC, compared with sham treatment, signi cantly reduced the rate of AKI (P =0 .02) and actually reduced the proportions of stage II-III cases (P =0 .02) following cardiac surgery [7].…”
Section: Effect Of Remote Ischemic Preconditioning On Clinical Outcommentioning
confidence: 99%